PERAN NINIK MAMAK TERHADAP PENYANDANG DISABILITAS MENTAL PADA MASYARAKAT HUKUM ADAT KAMPAR - Humairah, Shania; Ismi, Hayatul; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The role of Ninik Mamak in the midst of society to lead nephews is a dream in all fields which include morals and material. Ninik Mamak in a custom is the judge of peace when there is a dispute in the people he leads. Based on this, Ninik Mamak as the traditional leader is required to improve his knowledge in the field of leadership and customary law. As Ninik Mamak, of course he has duties and responsibilities that cannot be said lightly. Because these tasks are related to the survival of their people. Including the case of persons with mental disabilities, the role of Ninik Mamak is also needed. How does Ninik Mamak provide motivation and provide material and non-material assistance to his nephews. The purpose of writing this thesis, namely, first to find out how the role of Ninik Mamak for people with mental disabilities in the Kampar customary law community, and second to find out the obstacles faced by Ninik Mamak in carrying out his role for people with mental disabilities in the Kampar customary law community.This type of research is sociological legal research. This study is more specific to seeing law in a real sense and examining how law works in society by analyzing various literatures related to the problem being studied. The research was conducted in Kampar Regency, while the population and sample were the Village Head of Kampar Regency, Ninik Mamak, Kampar Regency, and families of persons with mental disabilities in Kampar Regency, the data sources used were primary data and secondary data, data collection techniques in this study were interview observation and literature study.From the results of the research conducted, it can be concluded that, first, the role of Ninik Mamak towards persons with mental disabilities in the Kampar customary law community does not necessarily work as it should. Second, the obstacles that Ninik Mamak encountered in his role for people with mental disabilities in the Kampar customary law community were Ninik Mamak who had migrated, the quality of Ninik Mamak's human resources (HR) who was not competent and the economic limitations of a Ninik Mamak could forget his duties and functions to his children.Keywords: Role-Ninik Mamak-Persons with Mental Disabilities